Are ch4, co2, and n2 o emissions from soil affected by the sources and doses of n in warm-season pasture? - da Cruz Corrêa, Darlena Caroline [UNESP]; Cardoso, Abmael da Silva [UNESP]; Ferreira, Mariane Rodrigues [UNESP]; Siniscalchi, Débora [UNESP]; Toniello, Ariana Desie [UNESP]; de Lima, Gilmar Cotrin [UNESP]; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Claudia [UNESP] (MDPI, 2021)
The intensification of pasture production has increased the use of N fertilizers—a practice that can alter soil greenhouse gas (GHG) fluxes. The objective of the present study was to evaluate the fluxes of CH4, CO2, and N2 O in the soil of Urochloa brizantha ‘Marandu’ pastures fertilized with different sources and doses of N. Two field experiments were conducted to evaluate GHG fluxes following N fertilization with urea, ammonium nitrate, and ammonium sulfate at doses of 0, 90, 180, and 270 kg N ha−1 . GHG fluxes were quantified using the static chamber technique and gas chromatography. In both experiments, the sources and doses of N did not significantly affect cumulative GHG emissions, while N fertilization significantly affected cumulative N2 O and CO2 emissions compared to the control treatment. The N2 O emission factor following fertilization with urea, ammonium nitrate, and ammonium sulfate was lower than the United Nations’ Intergovernmental Panel on Climate Change standard (0.35%, 0.24%, and 0.21%, respectively, with fractionation fertilization and 1.00%, 0.83%, and 1.03%, respectively, with single fertilization). These findings are important for integrating national inventories and improving GHG estimation in tropical regions.
Keywords: Brachiaria grass; GHG; Livestock; Marandu fertilization; Mitigation; N fertilization; Nitrous oxide; Soil methane; Soil respiration